MicroRNA-141 and MicroRNA-200c Are Overexpressed in Granulosa Cells of Polycystic Ovary Syndrome Patients - He, Tingting; Liu, Yuan; Jia, Yueyue; Wang, Haiyan; Yang, Xiao; Lu, Gang; Liu, Hongbin; Shi, Yuhua (Frontiers in Medicine, 2018)
Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in reproductive-aged women, affecting 6-8% of women and characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology. Accumulating evidence demonstrates that different microRNAs (miRNAs) expressions may contribute to the pathogenesis of PCOS. Therefore, the goal of this study is to compare the expression levels of miR-141 and miR-200c in granulosa cells isolated from PCOS patients and also evaluate their predictive values for pregnancy complications. First, RNA extraction, reverse transcription, and reverse transcription-polymerase chain reaction (RT-PCR) were performed to assess the expression levels of miR-141 and miR-200c in granulosa cells isolated from 62 PCOS patients and 61 controls. Second, according to each mean of miR-141 and miR-200c measured values in all patients, PCOS and controls were divided into low-expression group and high-expression group to better evaluate their predictive values for pregnancy complications. Significantly elevated expressions of miR-141 and miR-200c were observed in PCOS patients compared with the controls (p < 0.001 and p=0.002, respectively). Furthermore, PCOS patients had a significantly increased incidence of pregnancy complications in low-expression groups of miR-141 and miR-200c (p =0.007 and p=0.002, respectively). Our findings demonstrated that the expressions of both miR-141 and miR-200c were significantly increased in PCOS patients, which might contribute to the pathogenesis of PCOS. PCOS patients had an increased risk of pregnancy complications in low-expression groups of both miR-141 and miR-200c.